PRINSIP PIAGAM MADINAH DALAM KURIKULUM MERDEKA DI MADRASAH ALIYAH SIROJUL FALAH - Syahril Alamsyah; Edy; Alek Maulana; Ahmad Sofyan; Muhamad Rochmansyah (Khidmatussifa: Journal of Islamic Studies, 2025)
This writing is motivated by a problem that has become a criticism of Islamic Religious Education on the basis of failure in freeing students from a number of intolerant behaviors. These diversity. So that this study is intended to find out that Madrasah Aliyah Sirojul Falah as a representative of Islamic Religius Education has a form of integration of the principles of the Medina Charter as a representive of Islamic teaching that are rich in diversity and tolerance. This study use a type of literature study and field observation research with a qualitative descriptive approach. In collecting data, the researcher used documentation, interview, and observation methods consisting of primary sources, namely the curriculum of Madrasah Aliyah Sirojul Falah and secondary sources, namely the book Sirah Nabawiyah by Ibn Hisyam and other supporting books related to the discussion. This data analysis used includes data reduction, data presentation, and data verification. This results of the study show that the principles of the Medina Charter consisting of nationality, unity, equality, freedom, and mussyawarah in factual conditions are integrated into the curriculum of Madrasah Aliyah Sirojul Falah through three forms; 1) Forms of learning; 2) Forms of activities outside of learning; 3) Extracurricular forms.